Concurrent feedback versus terminal feedback: The investigation in improving throwing accuracy in handball among primary student / Wan Habshah Wan Omar - Wan Omar, Wan Habshah (Faculty of Sport Science and Recreation, 2018)
The acquisitions of motor skills are fundamental in human life. Feedback is related with the learning of motor skills. The study regarding on the effects of feedback on motor learning is inconclusive. Therefore, this study was conducted to compare the effectiveness between concurrent feedback and terminal feedback on the throwing accuracy in handball. A total of twenty-two (N=22) primary male students with no health problems, (age, 10.91 ±O.29; weight, 36.90±10.99; height, 1.44±0.07) involved in this study. Subjects were divided into two different feedback groups: concurrent feedback group and terminal feedback group. Feedback was given during the execution of the skill for concurrent feedback group and feedback were given after finish the training for terminal feedback group. Based on Repeated Measure ANOVA, it shows insignificant result between the two groups. Although the result shows insignificant findings between the two groups, it shows the improvements in the skills among concurrent group participants due to the strengths of understanding and the ability to retain information that they received. Therefore, it is suggested that a concurrent feedback shows greater improvement compared to terminal feedback.